PENGARUH MOTIVASI, PERSEPSI MAHASISWA DAN PENERAPAN E-LEARNING TERHADAP PENINGKATAN KUALITAS PENDIDIKAN TINGGI - Astitiani, Ni Luh Putu Surya; Richadinata, Kadek Riyan Putra (E-Jurnal Manajemen; Vol 10 No 1 (2021)DO - 10.24843/EJMUNUD.2021.v10.i01.p03, 2021)
The field of education has now been influenced by the development of digital information technology where technological developments can improve performance and allow various activities to be carried out quickly, precisely and accurately, thereby increasing productivity. Information technology has served as a supplier of knowledge. The rapid advancement of technology must be balanced with efforts to improve the quality of education and knowledge. This study was conducted to determine the effect of motivation, student perceptions and the application of E-Learning on improving the quality of higher education at the University of Bali International. The sample in this study were 120 students at the University of Bali International where the results of data collection were processed using Multiple Regression analysis. The results of the study prove that motivation, student perceptions and the application of E-Learning have a positive and significant effect on improving the quality of higher education at the University of Bali International. This shows that the quality of higher education can increase not only influenced by technological advances, namely by the application of E-Learning but the motivation and perceptions of students can also improve the quality of higher education itself.